The Effect of Information Disclosure on Information Asymmetry - CHIYACHANTANA, Chiraphol New (Institutional Knowledge at Singapore Management University, 2013)
This study investigates the relation among information disclosure, firm characteristics and information asymmetry. The authors find evidence consistent with the notion that increasing corporate disclosure and transparency reduces the asymmetric information between informed and uninformed investors. The findings indicate a strong relation between firm characteristics and level of information disclosure. Larger firms, firms with high growth opportunity and superior performance are associated with higher level of information disclosure. With respect to type of information, large firms, firms with superior operating performance, high growth opportunity are likely to disclose the investment and structural change as well as legal and miscellaneous information. Furthermore, the empirical findings indicate that listed companies with high corporate transparency and disclosure have low relative bid-ask spreads and high share turnover. Conclusively, the evidence supports the notion that increasing corporate disclosure and transparency reduce the asymmetric information between informed and uninformed traders.